2005
DOI: 10.1266/ggs.80.403
|View full text |Cite
|
Sign up to set email alerts
|

Male-fertility genes expressed in male flower buds of Silene latifolia include homologs of anther-specific genes

Abstract: When the female plant of Silene latifolia is infected with the smut fungus Microbotryum violaceum , its rudimentary stamens develop into anthers which contain fungus teliospores instead of pollen. To identify genes required for maturation of anthers in S. latifolia , we performed a cDNA subtraction approach with healthy male buds and female buds infected with M. violaceum . We isolated five cDNA clones, which were preferentially expressed in healthy male buds during stages associated with a burst in tapetal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 52 publications
0
23
0
Order By: Relevance
“…In addition, the expression of several APG (a Pro-rich protein)-like genes was altered in ams (see Supplemental Data Set 1 online). The tapetum-specific APG gene in Silene latifolia was previously shown to be associated with the development of fertile pollen (Ageez et al, 2005).…”
Section: Ams Alters the Expression Of Genes Required For Tapetal Diffmentioning
confidence: 99%
“…In addition, the expression of several APG (a Pro-rich protein)-like genes was altered in ams (see Supplemental Data Set 1 online). The tapetum-specific APG gene in Silene latifolia was previously shown to be associated with the development of fertile pollen (Ageez et al, 2005).…”
Section: Ams Alters the Expression Of Genes Required For Tapetal Diffmentioning
confidence: 99%
“…We also retrieved the PKS-related Nicotiana sylvestris CHSLK, Silene latifolia Chs, and Pinus radiata CHS1 genes, previously shown to have high expression in male flowers or anthers (Atanassov et al, 1998;Walden et al, 1999;Ageez et al, 2005) and generated an unrooted maximum likelihood tree of aligned CHS and PKS-related protein sequences. This analysis, shown in Figure 1, indicated that PKSA and PKSB are located in two distinct PKS subclades that are clearly distinct from the more distantly related clade containing the bona fide Arabidopsis and Physcomitrella CHS genes and other putative CHS genes from poplar and rice.…”
Section: Pksa and Pksb-like Genes Are Conserved In Land Plant Lineagesmentioning
confidence: 99%
“…The CHSL clade containing PKSA and PKSB has two distinct subclades of angiosperm PKS genes that are related to either Arabidopsis PKSA or PKSB, with at least one PKSA and one PKSB homolog found in each of the fully sequenced poplar and rice genomes. In addition, the N. sylvestris PKSA homolog CHSlk (Atanassov et al, 1998) and S. latifolia PKSB homolog CHSL (Ageez et al, 2005) are known to be expressed in male reproductive organs, and the wheat and triticale homologs of the Arabidopsis PKSs also have anther and tapetum-preferred expression patterns (Wu et al, 2008).…”
Section: Conservation Of Pksa and Pksb Functions In A Sporopollenin Pmentioning
confidence: 99%
“…In contrast, LAP5, LAP6, and At4g00040 share only 40% sequence identity with the Arabidopsis CHS TT4 or with CHSs from other organisms. However, they share 64% (LAP5-LAP6), 76% (At4g00040-LAP5), and 62% (At4g00040-LAP6) identity with each other and are members of a male-organ-specific CHS-like protein clade, which includes proteins from dicots, monocots, and gymnosperms (BA42 from Brassica napus [Shen and Hsu, 1992], YY2 from rice [Oryza sativa; Hihara et al, 1996], SlCHS from Silene latifolia [Ageez et al, 2005], and CHSLK from Nicotiana sylvestris [Atanassov et al, 1998]; Fig. 3).…”
Section: Lap5 and Lap6 Encode Chs Superfamily Proteinsmentioning
confidence: 99%